Rethinking Classroom Ventilation in post pandemic Situation - Harwahyu, Ruki; Setiani, Hastin; Faroghi, Muhammad Surya; Sari, Riri Fitri (Universitas Diponegoro, 2022)
This paper aims to contribute in outlining the latest findings and formulating a simple practice in providing sufficient air circulation for classroom activities in preparation for the post-pandemic era. During this pandemic, remote learning over the internet has been a viable solution everywhere, including adopted by education institution to keep serving the learning process. However, as more and more people involved and the time elapses, several disadvantages of e-learning are realized. In addition, education institution should be prepared for the upcoming offline learning activity in post-pandemic era. This paper aims to refine the minimum airflow requirement for the classroom, finetuned based on student activity, ceiling height. Student activity is being the focus rather than teacher because student represents the majority of classroom occupant. In addition, a discussion on how it can be achieved using simpler ventilation system is presented. ON/OFF scheme for the usage of the active ventilation is also elaborated.Keyword: classroom, post-pandemic era, ventilation system, air circulation.